2006
DOI: 10.1636/s04-30.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of Three Brazilian Goniosoma Species: A New Record for Diploid Number in Laniatores (Opiliones, Gonyleptidae, Goniosomatinae)

Abstract: Currently, 60 species of harvestmen have been karyotyped and all of these are from the Nearctic and Palearctic regions. This work is the first cytogenetic report of three gonyleptid species of the suborder Laniatores: Goniosoma aff. badium, G. proximum and G. spelaeum of the Neotropical region, from the southeastern region of Brazil. Conventional Giemsa stain chromosome preparations were obtained from embryonic cells and adult male testes. Embryo mitotic plates of G. aff. badium and G. proximum indicated 88 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
2
12
2
1
Order By: Relevance
“…2002). The high diploid number herein recorded in D. pectinifemur was also reported in four laniatorean species previously analysed by Cokendolpher and Jones (1991) and Oliveira et al. (2006).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…2002). The high diploid number herein recorded in D. pectinifemur was also reported in four laniatorean species previously analysed by Cokendolpher and Jones (1991) and Oliveira et al. (2006).…”
Section: Discussionsupporting
confidence: 85%
“…The NOR distribution pattern observed in D. pectinifemur differed from that detected in the other species of Gonyleptidae whose chromosomes were analysed (Oliveira et al. 2006).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The number and location of NORs were only established, for example, in approximately 30 species of Araneae (Král et al, 2006;Král, 2007;Oliveira et al, 2007;Rodríguez-Gil et al, 2007;Araujo et al, 2008;Stávale et al, 2010Stávale et al, , 2011Dolejš et al, 2011;Král et al, 2011), 17 species of Scorpiones (Schneider et al, 2009a,b;Schneider and Cella, 2010), 3 species of Opiliones (Gorlov and Tsurusaki, 2000;Oliveira et al, 2006;Schneider et al, 2008;Mattos et al, 2013), and two species of Palpigradi (Král et al, 2008). In almost all these species, the NORs were only identified through the use of silver impregnation; however, in an overview of the NOR distribution in Coleoptera, Schneider et al (2007) showed that the results were usually coincident when the chromosomes were examined with both silver impregnation and FISH technique.…”
Section: Discussionmentioning
confidence: 99%
“…In harvestmen, the number and the distribution of rDNA loci have up to now only been examined by means of silver staining of nucleolar argyrophilic proteins, hence detecting only transcriptionally active rDNA clusters [Gorlov and Tsurusaki, 2000b;Oliveira et al, 2006;Schneider et al, 2008]. Only a single rDNA cluster was visualized in a diploid set of Psathyropus tenuipes (L. Koch, 1878) (Sclerosomatidae) [Gorlov and Tsurusaki, 2000b] and Dyscocyrtus pectinifemur (Mello-Leitão, 1937) (Gonyleptidae) [Schneider et al, 2008], while 1 pair of rDNA loci was noted in Goniosoma spelaeum (Mello-Leitão, 1932) [Oliveira et al, 2006]. In other arachnid orders, the data on the number and the position of rDNA are still fragmentary, too.…”
Section: Discussionmentioning
confidence: 99%